2022
DOI: 10.3390/coatings12101480
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Aloe vera Gel as Coating Agent to Maintain the Quality of Tomatoes during Storage

Abstract: Aloe vera is widely used to manufacture medicinal products, cosmetics, and hair treatments. The polysaccharide components in A. vera gel can be used as ingredients for edible films or coatings. The edible film can also be applied to fresh fruits and vegetables using the coating principle. Tomatoes are one of the fruit commodities that can be maintained in terms of quality during storage using an edible coating. This study aims to determine the effect of an edible coating made from A. vera on tomatoes’ physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
0
3
0
1
Order By: Relevance
“…Aloe vera is used as a plasticizer that can decrease weight loss and inhibit the maturity stage, as shown in the titratable acidity, pH, and total soluble solids. It has also been studied in several foods, such as tomatoes [25] and apples [185]. The authors showed that aloe vera could minimize the degradation of phenolic and flavonoid compounds and protect the ability of tomatoes to act as an antioxidant, and the application in apples showed an attractive natural shine quite similar to that of freshly harvested fruit.…”
Section: Using Essential Oils Plasticizers Extracts and Crosslinker A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Aloe vera is used as a plasticizer that can decrease weight loss and inhibit the maturity stage, as shown in the titratable acidity, pH, and total soluble solids. It has also been studied in several foods, such as tomatoes [25] and apples [185]. The authors showed that aloe vera could minimize the degradation of phenolic and flavonoid compounds and protect the ability of tomatoes to act as an antioxidant, and the application in apples showed an attractive natural shine quite similar to that of freshly harvested fruit.…”
Section: Using Essential Oils Plasticizers Extracts and Crosslinker A...mentioning
confidence: 99%
“…Edible coatings are made from natural food-grade materials, such as hydrocolloids (polysaccharides, proteins), lipids, and emulsifiers, produced with different techniques, such as dipping (immersing), spraying, spreading, brushing, pressing them/thermoforming, or extrusion [24][25][26]. The most used technique for coating is immersing, where food is dipped in a liquid containing food matrices, forming a film around the food and protecting all the components present.…”
Section: Introductionmentioning
confidence: 99%
“…Las variables pH y conductividad eléctrica no presentaron diferencias significativas por la aplicación de gallinaza. El contenido de SS está relacionado con el incremento de la degradación de los polisacáridos que forman la membrana celular, incrementando el contenido de azúcares disueltos (Jati et al 2022). El valor máximo de SS al aplicarse gallinaza (9.89%) supera a los reportados por Crisanto-Juárez et al…”
Section: )unclassified
“…Aloe vera (Liliaceae family plant) was used for carrageenan-based films to provide antibacterial properties for films. It is widely used in pharmaceuticals, cosmetics, and food products such as drinks and snacks [32]. It has excellent tolerance to drought conditions due to the ability to absorb and retain water for a longer time [33].…”
Section: Introductionmentioning
confidence: 99%